Strategies to Create a Writing Group as a Cooperative Learning Space - Hermosura, Billie Jane C.; McGinnis, Sarah; Steventon, Joanne (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes, 2025)
Examining the significance of academic collaborative spaces, specifically writing groups, in supporting the progress of doctoral students, this Field Notes focuses on the challenges posed by the onset of the COVID-19 pandemic. The authors share personal narratives as two doctoral students, Author1 and Author2, who encountered unique circumstances during the pandemic and successfully navigated them by establishing an online co-working community. Grounded in self-determination theory, the authors highlight the importance of addressing the psychological needs of autonomy, competence, and relatedness within a peer writing group. They propose strategies for developing and maintaining relatedness, such as making online acquaintances, building a community, fostering camaraderie, and incorporating a mentorship component. The findings emphasize the significance of consistency, adaptability, and transitioning from online to in-person interactions. The authors conclude with recommendations for graduate students seeking to establish writing groups, emphasizing shared goals, community building, and the passing on of knowledge and mentorship. Overall, this exploration provides valuable insights into creating effective online collaborative spaces for doctoral students, especially in the face of unprecedented challenges like the global pandemic.